Analysis of Government Efforts to Handle Declining Petroleum Yields in Indonesia - Mekkah Najwa Pury; Nastiti Catur Istiqomah; Kejora Lintang Kusuma Astutiningsih; Moh. Aris Munandar; Hafiz Rafi Uddin (International Journal of Sustainable Applied Sciences, 2024)
All existing innovations continue to be developed by both the government and the community to obtain future savings frHom petroleum products for the next year. The purpose of this research is to analyze how the government innovates in maintaining the limitations and availability of petroleum materials in Indonesia and the impact on how to handle the issue of petroleum problems. The discussion in this article covers the factors of depletion of Indonesia's petroleum reserves, how innovations are carried out, and the impacts they have. This analysis refers to electronic journals that can be accounted for based on discussions of the government's efforts to deal with the decline in petroleum output in Indonesia. The methodology used is a quantitative descriptive method to analyze the issues to be discussed. The data obtained came from journals using skill-free listening (SLBB) and note-taking techniques. Researchers understand the contents of the journals obtained and the results are in the form of notes with correct accountability. It is hoped that the analysis in this article will be able to increase insight and understanding, especially regarding innovations from the government and the people in dealing with the decline in petroleum output, and be able to provide a guide for readers to criticize the results of this article.